A comparison of retention capability of different fiberglass filters used for the determination of chlorophyll-a in coastal waters - Ahmad Manbohi; Sara Gholamipour; Gholamreza Mohammadpour (علوم محیطی)
Introduction: Filtration is one of the most important steps in phytoplankton studies. Choosing a filter for research purposes depends on its pore size and price. In the present study, the results obtained by Whatman, CHM, and BOECO filters were compared to find better filters to use in marine research.Material and methods: The samplings were performed in 6 stations of coastal waters of Bushehr port in winter (2017). The samples were filtered with the mentioned filters. After calorimetrical measurement of chlorophyll-a, the obtained results were compared. The Kolmogorov-Smirnov test was used to determine data distribution. In order to evaluate whether the differences are significant, the probability size criterion was used with the P <0.05 test level.Results and discussion: In most stations, the lowest amount of chlorophyll-a was obtained by the CHM filter. In most stations, the retention amount of chlorophyll-a using the BOECO filter was higher than other filters. Despite the CHM filter, the results obtained using BOECO and Whatman filters were not significantly different (P>0.05). Therefore, the BOECO filter can be a good alternative to the expensive Whatman filter for research on phytoplanktons. Furthermore, for measuring suspended particulate matter, all three filters can be used.Conclusion: Due to the fact that the retention amounts of chlorophyll-a using the three filters were different, caution should be exercised when comparing chlorophyll-a results. It is also recommended that the Whatman filter be used in biological studies that rely on burning carbon and nitrogen on the filter.